Typed letter from Theo. Presser Co. to Emil A. Bertl - Theodore Presser Co.:::Creator::::::::::::; Bertl, Emil A., 1895-1982:::Contributor:::::::::::: (Philadelphia, 2021)
Typed letter from Theo. Presser Co. to Emil A. Bertl dated January 22, 1917, regarding placing bids for Beethoven relics by mail.